A simplified bacterial community found within the epidermis than at the epidermal surface of atopic dermatitis patients and healthy controls - Christopher J. Barnes; Maria Asplund; Maja-Lisa Clausen; Linett Rasmussen; Caroline Meyer Olesen; Yasemin Topal Yüksel; Paal Skytt Andersen; Thomas Litman; Kim Holmstrøm; Lene Bay; Blaine Gabriel Fritz; Thomas Bjarnsholt; et al. (BMC Microbiology, 2023)
Abstract There has been considerable research into the understanding of the healthy skin microbiome. Similarly, there is also a considerable body of research into whether specific microbes contribute to skin disorders, with atopic dermatitis (AD) routinely linked to increased Staphylococcus aureus (S. aureus) colonisation. In this study, the epidermal surface of participants was sampled using swabs, while serial tape-stripping (35 tapes) was performed to sample through the stratum corneum. Samples were taken from AD patients and healthy controls, and the bacterial communities were profiled by metabarcoding the universal V3-V4 16S rRNA region. Results show that the majority of bacterial richness is located within the outermost layers of the stratum corneum, however there were many taxa that were found almost exclusively at the very outermost layer of the epidermis. We therefore hypothesise that tape-stripping can be performed to investigate the ‘core microbiome’ of participants by removing environmental contaminants. Interestingly, significant community variation between AD patients and healthy controls was only observable at the epidermal surface, yet a number of individual taxa were found to consistently differ with AD status across the entire epidermis (i.e. both the epidermal surface and within the epidermis). Sampling strategy could therefore be tailored dependent on the hypothesis, with sampling for forensic applications best performed using surface swabs and outer tapes, while profiling sub-surface communities may better reflect host genome and immunological status.